Temyracle / Adilah Hanim Aznam and Nuranis Syahirah Mohd Fakhrurrozi - Aznam, Adilah Hanim; Mohd Fakhrurrozi, Nuranis Syahirah (2022)
For ENT530 course, we created Facebook page to advertise our business through online. We registered as a dropship and choose Temyraclebyad for our Facebook name. Temyraclebyad are handled by Nuranis Syahirah and Adilah Hanim. We offers a customer with various homemade scrubs for the body and face. Our target market more focusing on women and men who want to have beautiful skin, glowing, white, acne-free & scars. We strive to provide the best natural scrub at an affordable price. Our products are believed to be safe & free from harmful chemicals because the ingredients used are only natural & organic ingredients. Lastly, we hope Temyracle will become a tremendous success in the future and be well-known around the world.